GAMBARAN PARTISIPASI IBU YANG MEMPUNYAI BALITA DALAM MENGIKUTI KEGIATAN POSYANDU DI RT 0 3 / RW XII PONDOK WAGE INDAH II SIDOARJO - Ni Putu Widari (Jurnal Keperawatan, 2014)
Community participation was actively participate in the process or workflow steps and monitoring programs ranging from the promotion phase, planning, implementation, and preservation activities by donating energy, thought, or in the form of material. There are several factors that affect the mother's participation in the following activities, namely Posyandu: education, age, occupation, and the order of the child in the family. The purpose of this study was to determine the level of activity in the capital following the activities of Posyandu in RT 03 / RW XII Wage Pondok Indah II Sidoarjo. This study uses a descriptive design. The method used is total sampling. Collecting data using questionnaires. The collected data was then tabulated manually. Based on the results of the study, the data obtained in the active respondents who participated in the Posyandu were 12 respondents (40%), and were not active as much as 18 respondents (60%), from these data it can be concluded that participation in the following activities have toddlers Posyandu is not active . Therefore these results are an input to the Posyandu to provide information that promotes participation Posyandu mother to visit.